(untitled) (Journal of Management and Social Sciences, 2026)
As artificial intelligence (AI) and digital surveillance technologies reshape governance systems worldwide, their impact on migration extends beyond efficiency and security to the very core of migrant identity and belonging. This conceptual paper critically examines how AI, biometric systems, and predictive analytics influence migrants’ access to rights, cultural negotiation, and social inclusion. Grounded in Technological Determinism Theory, the study employs a thematic synthesis of peer-reviewed literature, policy reports, and migration data published between 2010 and 2025. Findings reveal that migrant identity is shaped by the interplay of legal recognition, cultural belonging, and technological mediation. While AI-driven systems streamline migration processes in developed economies, they often reproduce biases, heighten surveillance, and restrict agency. In contrast, uneven adoption in emerging economies, particularly in Africa, creates hybrid governance spaces where migrants navigate both formal and informal systems. Across regions, migrants actively negotiate identity through community networks, cultural hybridity, and resistance to digital profiling, demonstrating agency in the face of technological constraints. The study concludes that AI is not a neutral tool but a powerful determinant of how migrants are categorized, included, or excluded in contemporary societies. It recommends that migration governance balance technological efficiency with ethical safeguards, robust data protections, and inclusive policies that uphold migrants’ rights and sense of belonging. Keywords: Artificial intelligence, migrant identity, digital surveillance, technological determinism, migration governance, Africa